Risk Analysis Using HIRADC Method (Hazard Identification Risk Assessment and Determining Control) in the Palm Oil Processing Plant of PT. Perkebunan Nusantara VII Unit Bekri Lampung Tengah - Hasiany, Sillak; Difa, Geta Fatonah; Awan, Fajriharish Nur; Prasetio, Bambang (World Chemical Engineering Journal, 2024)
The palm oil processing plant of PT. Perkebunan Nusantara VII Unit Bekri Lampung Tengah is subject to various risks that need to be identified and assessed for effective control measures. This research aims to conduct a comprehensive risk analysis using the HIRADC (Hazard Identification Risk Assessment and Determining Control) method in the palm oil processing plant. The study involves the identification of hazards, assessment of risks associated with these hazards, and the determination of appropriate control measures. Data for the risk analysis are collected through literature review, field observations, interviews, and questionnaire surveys. The results of the analysis highlight the identified risks and their corresponding risk levels. The risk analysis reveals 10 work areas with 4 types of risk hazards and 84 risk identifications, categorized as 22 high-level risks, 13 medium-level risks, and 49 low-level risks By applying the HIRADC method, suitable control measures are recommended based on the hierarchyof risk control, including hazard elimination, engineering controls, administrative controls, and the use of personal protective equipment. This research provides valuable insights into risk management practices in the palm oil processing industry, specifically in PT. Perkebunan Nusantara VII Unit Bekri Lampung Tengah, and can serve as a foundation for improving occupational safety and health in similar industrial settings.